The Role of Digital Innovation in Islamic Religious Education Learning to Strengthen Religious Literacy in School Students - Irmiati, Rahma Aulia; Putri, Hany Lidya (Fakultas Tarbiyah dan Ilmu Keguruan, Universitas Islam Negeri (UIN) Syekh Wasil Kediri, Indonesia, 2025)
The advancement of digital technology has significantly transformed the landscape of education, including the teaching and learning of Islamic Religious Education (PAI). Digital innovations, particularly through the utilization of various media and technological platforms, offer strategic opportunities to enhance religious literacy among school students. This study aims to examine the role of digital innovation in improving the effectiveness of PAI learning, as well as to explore the challenges and potential solutions in its implementation. Employing a library research method with a qualitative descriptive approach, this article reveals that the use of digital tools—such as interactive learning applications and educational social media—can enrich teaching methods, increase student engagement, and strengthen understanding of Islamic values. However, issues such as unequal access to technology, low digital literacy, and digital distractions remain critical obstacles that require comprehensive solutions. Therefore, collaboration among educators, schools, policymakers, and parents is essential to develop an adaptive and character-oriented digital learning environment. This study recommends the development of holistic and contextual digital-based Islamic education policies and learning models.